Cooperative banks in social media – a survey of activities based on customer relations - Tomczyk, Kamila (Banki spółdzielcze w mediach społecznościowych – badanie aktywności na podstawie relacji z klientem, 2021)
Social media has become an integral part of the life of modern society. Facebook is the most popular communicator in its role of sharing information with friends. Developing need banks to establish relations with current and future customers. The presented business cycle research proves that many financial institutions are not convinced about conducting research in social media.
Informatyka Ekonomiczna = Business Informatics, 2021, Nr 4 (62), s. 37-50
Keywords: social media; Facebook; cooperative banks; Customer Relationship Management; media społecznościowe; banki spółdzielcze; zarządzanie relacjami z klientem